The Multidirectional Influence of Feed-Borne Deoxynivalenol and Zearalenone on Animal Health - Maciej T. Gajęcki; Magdalena Gajęcka (Toxins, 2023)
Mycotoxins are secondary fungal metabolites which pose a significant threat for global food and feed security [...]